Decision Support Systems VII. Data, Information and Knowledge Visualization in Decision Support Systems : Third International Conference, ICDSST 2017, Namur, Belgium, May 29-31, 2017, Proceedings /: Third International Conference, ICDSST 2017, Namur, Belgium, May 29-31, 2017, Proceedings. (2017) - Unknown
No abstract available